Fixed-dose combination of indacaterol/glycopyrronium/mometasone furoate once-daily versus salmeterol/fluticasone twice-daily plus tiotropium once-daily in patients with uncontrolled asthma: A randomised, Phase IIIb, non-inferiority study (ARGON). (August 2020) - Gessner, Christian; Kornmann, Oliver; Maspero, Jorge; van Zyl-Smit, Richard; Krüll, Matthias; Salina, Anna; Gupta, Pritam; Bostel, Sebastien; Fucile, Sebastian; Conde, Lorena Garcia; Pfister, Pascal
Abstract: Background: The efficacy and safety of once-daily (o.d.) fixed-dose combination of indacaterol (IND), glycopyrronium (GLY) and mometasone furoate (MF) via Breezhaler® versus concurrent administration of salmeterol/fluticasone (SAL/FLU) twice-daily (b.i.d.) via Accuhaler®+Tiotropium (TIO) o.d. via Respimat® was evaluated in patients with uncontrolled asthma. Methods: Patients (aged ≥18 years), symptomatic (Asthma Control Questionnaire [ACQ]-7 ≥1.5) despite treatment with long-acting β2 -agonist/inhaled corticosteroid medium- or high-dose, received IND/GLY/MF high- (150/50/160 μg) or medium-dose (150/50/80 μg) o.d. or SAL/FLU high-dose (50/500 μg) b.i.d.+Tio 5 μg o.d. for 24 weeks. The primary objective was to confirm the non-inferiority of either dose of IND/GLY/MF to SAL/FLU high dose + TIO in terms of Asthma Quality of Life Questionnaire (AQLQ). Additional endpoints: ACQ-7, lung function, health status (St George's Respiratory Questionnaire [SGRQ]), exacerbations, and safety after 24 weeks. Results: IND/GLY/MF high- and medium-dose met the primary endpoint, confirming non-inferiority to SAL/FLU high dose + TIO for AQLQ (least square mean treatment difference [Δ]: 0.073 and −0.038, respectively; both p < 0.001). IND/GLY/MF high-dose improved ACQ-7 (Δ: −0.124; p = 0.004), trough FEV1 (Δ: 96 mL; p < 0.001), peak expiratory flow (morning [Δ: 9.56 L/min; p = 0.005], evening [Δ: 9.15 L/min; p = 0.006]) and SGRQ (Δ: −2.00; p = 0.04) versus SAL/FLU high dose + TIO. Improvements in these endpoints were comparable for IND/GLY/MF medium-dose and SAL/FLU high dose + TIO. Adverse events were generally comparable across treatments. Conclusions: IND/GLY/MF high- and medium-dose o.d. via a single inhaler were non-inferior to SAL/FLU high-dose b.i.d. + TIO o.d. via two inhalers for AQLQ. IND/GLY/MF high-dose o.d. improved lung function, asthma control and health status versus SAL/FLU high dose + TIO, while IND/GLY/MF medium-dose had comparable efficacy but at a corresponding lower steroid dose. Highlights: IND/GLY/MF high- and medium-dose met the primary endpoint, confirming non-inferiority to SAL/FLU high-dose + TIO for AQLQ. IND/GLY/MF high-dose improved ACQ-7, trough FEV1, peak expiratory flow versus SAL/FLU high-dose + TIO. IND/GLY/MF high-dose improved SGRQ versus SAL/FLU high-dose + TIO. IND/GLY/MF medium-dose had comparable efficacy but at a corresponding lower steroid dose.